Peran Guru dalam Mengembangkan Achievement Motivation Melalui Mata Pelajaran PPKn dengan Model Project Based Learning (Pjbl) Kelas VIII Di SMPN 3 Trenggalek Semester - Juwito, Reza Hamdan; Dirgantoro, Adjar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study examines the role of teachers as motivators and facilitators in the implementation of the Project-Based Learning (PjBL) model, particularly in the subject of Pancasila and Civic Education (PPKn) at SMP Negeri 3 Trenggalek, focusing on eighth-grade students during the odd semester of the 2024/2025 academic year. In this context, teachers play a crucial role in motivating students to actively engage in the learning process, while also facilitating the development of their knowledge and skills through a project-based approach. The aim of this research is to explore how teachers understand students’ characteristics and identify the key roles they must assume to create a supportive learning environment. This study employs a qualitative method, using direct interviews with teachers and students, which are then analyzed to gain insights into the effectiveness of the teacher’s role within the PjBL model. The findings are expected to provide a deeper understanding of the importance of teachers’ roles in motivating and facilitating students in project-based learning. Supporting factors in the use of the PjBL method to enhance students’ achievement motivation include well-equipped school facilities and competent school community resources capable of fulfilling their responsibilities. On the other hand, the inhibiting factors include an unconducive school environment, lack of parental support, and poor emotional conditions of both educators and students.